PENDAMPINGAN FERMENTASI LIMBAH BATANG PISANG SEBAGAI PAKAN ALTERNATIF SAPI DAN KAMBING DALAM MENINGKATKAN PEREKONOMIAN UMAT DI DESA TANJUNG ALAM KECAMATAN KINAL KABUPATEN KAUR - Sari, Anggun Nidia; Hak, Nurul; Alfiah, Esti (JURNAL ILMIAH EDUNOMIKA, 2024)
The lack of use of banana stems, which are quite a lot around the community, can be processed into something more useful, rather than just left as trash or litter under the banana trees. Tanjung Alam Village is a village in the Kinal District, Kaur Regency. Based on the results of a survey conducted by service providers, the residents of this village have several livestock but they are not growing very well because they are influenced by several factors such as the price of feed being too expensive and feed being difficult to obtain in the dry season. The research method used is community service. The results show that providing alternative feed in the form of banana tree stems is a good innovation in increasing livestock productivity. It is hoped that this service will be able to help cattle breeders in processing alternative feed, where previously banana stems were simply thrown away after being harvested. After the dedication, the number of banana stems that become waste reduces and reduces pollution of the community's environment and it is also hoped that it can improve the economic level of the community in overcoming the problems faced by breeders, so that livestock development in Tanjung Alam village is expected to be maximized.